The impact of ship emission controls recorded by cloud properties - Gryspeerdt,E; Smith,T; O'Keeffe,E; Christensen,M; Goldsworth,F (Geophysical Research Letters, 2019)
The impact of aerosols on cloud properties is one of the leading uncertainties in the human forcing of the climate. Ships are large, isolated sources of aerosol creating linear cloud formations known as shiptracks. These are an ideal opportunity to identify and measure aerosol-cloud interactions. This work uses over 17,000 shiptracks during the implementation of fuel sulphur content regulations to demonstrate the central role of sulphate aerosol in ship exhaust for modifying clouds. By connecting individual shiptracks to transponder data, it is shown that almost half of shiptracks are likely undetected, masking a significant contribution to the climate impact of shipping. A pathway to retrieving ship sulphate emissions is demonstrated, showing how cloud observations could be used to monitor air pollution.